GENDER FEATURES OF FORMS OF ADDRESS: A CONTRASTIVE ANALYSIS ENGLISH AND UZBEK LITERARY EXAMPLES (Journal of Universal Science Research, 2025)
This article explores the gender-specific features of address terms in Uzbek and English languages through a contrastive analysis of literary works: “Ufq” by Said Ahmad and “Death on the Nile” by Agatha Christie. While both languages share certain similarities in the use of pronominal form of address, significant differences exist in nominal forms of address, particularly in their expression of gender distinctions.